The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/ie0704748
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Nano CaO/Al2O3 CO2 Sorbent

Abstract: This project studied the properties of nano CaO/Al2O3 as a high-temperature CO2 sorbent for its use in an adsorption enhanced reforming reaction. The sorbent containing nano CaCO3 precursors and aluminum oxide was prepared, and evaluation of the CO2 adsorption properties by a thermogravimetric analyzer, the results show that nano CaO/Al2O3 has a faster decomposition rate and has a higher CO2 adsorption ratio than micro CaO/Al2O3. The maximum adsorption ratio occurs at temperatures of 650 °C under a CO2 partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(114 citation statements)
references
References 8 publications
(10 reference statements)
3
110
0
Order By: Relevance
“…SC-propane grafting apparatus. Lemonidou, 2008;Wu et al, 2008). Those obtained materials exhibited high adsorption capacities over 5 mmol/g in a temperature range from 600 and 700°C and long-term stability in cyclic runs which was attributed to the presence of Ca 12 Al 14 O 33 as the binder which inhibited the sintering of CaO particles.…”
Section: Other Adsorbentsmentioning
confidence: 93%
“…SC-propane grafting apparatus. Lemonidou, 2008;Wu et al, 2008). Those obtained materials exhibited high adsorption capacities over 5 mmol/g in a temperature range from 600 and 700°C and long-term stability in cyclic runs which was attributed to the presence of Ca 12 Al 14 O 33 as the binder which inhibited the sintering of CaO particles.…”
Section: Other Adsorbentsmentioning
confidence: 93%
“…limestone, dolomite), it makes sense to use the material over several cycles and to perform multiple regenerations before disposing of the used carbonate, so as to achieve genuine energy and CO 2 emissions reductions. Research efforts are taking place worldwide to understand the reasons for the loss of CO 2 capacity with repeated cycling and increase the durability of Ca-based CO 2 sorbent with this very aim [35][36][37][38][39][40][41][42][43]. Table 2 allows comparison of the minima of enthalpy changes of the urea-water system at 1 atm (and the temperatures at which they occur) with those of the urea-water-CaO system (with Ca:C=1), in kJ/mol of H 2 produced, alongside the H ratio, maxima of H 2 yield and of H 2 purity, also listed with their corresponding temperatures.…”
Section: Figurementioning
confidence: 99%
“…This is consistent with the SEM images that the hydration process breaks sintered sorbents into small pieces. Intra-particle spaces become larger with smaller grain size and thus become less CO 2 diffusion resistant (Wu et al 2008 ). Furthermore, it is found that hydration also alters the distribution of the surfaces in different orientations.…”
Section: Hydration and The Mechanism For Reactivationmentioning
confidence: 97%
“…Furthermore, when the nano-CaCO 3 precursor was mixed with other materials, both nano-sorbents and support effects are integrated together. For example, nano-CaO/Al 2 O 3 yields a stable adsorption ratio of 68.3 % after 15 cycles (Wu et al 2008 ). In addition, Ca 12 Al 14 O 33 forms at a lower temperature for the reaction between nano-CaCO 3 and Al 2 O 3 .…”
Section: Precursor and Support Materials Selectionmentioning
confidence: 99%